2011
DOI: 10.4028/www.scientific.net/kem.488-489.97
|View full text |Cite
|
Sign up to set email alerts
|

Crack Growth Rates and Corrosion Fatigue of Austenitic Stainless Steels in High Chloride Solutions

Abstract: Purpose: Applications for highly corrosive environments and cyclic loading are often made out of austenitic stainless steels. Corrosion fatigue and crack propagation behaviour has been studied to determine failure processes and damage mechanisms. Approach: CrNiMo stabilized austenitic stainless steel and CrMnN austenitic stainless steel in solution annealed and cold worked condition are compared. S/N curves and crack propagation rate curves are recorded in 43 wt% CaCl2solution at 120 °C, which resembles most s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In the studies of McEvily et al [ 37 , 38 ], the detrimental effect stemming from atmosphere seemed to dominate. Other authors also reported a decreased threshold value for austenitic stainless steels in environments like hydrogen, moist air, or chloride solutions [ 44 , 45 ]. As mentioned above, the data obtained in the present work cannot finally pinpoint the most dominant mechanism responsible for the observed kink in the d a /d N curves.…”
Section: Resultsmentioning
confidence: 98%
“…In the studies of McEvily et al [ 37 , 38 ], the detrimental effect stemming from atmosphere seemed to dominate. Other authors also reported a decreased threshold value for austenitic stainless steels in environments like hydrogen, moist air, or chloride solutions [ 44 , 45 ]. As mentioned above, the data obtained in the present work cannot finally pinpoint the most dominant mechanism responsible for the observed kink in the d a /d N curves.…”
Section: Resultsmentioning
confidence: 98%
“…The second, less widely spread group of austenitic stainless steels are the CrMnN austenites, where manganese is the alloying element that stabilizes the fcc lattice. CrMnN has been widely investigated by Speidel and Uggowitzer [ 20 , 21 ] and later by Mori and his group [ 22 , 23 ]. Manganese in contradiction to nickel is less noble than iron and behaves similarly to chromium with its electrochemical potential.…”
Section: Introductionmentioning
confidence: 99%